Understanding Generation Z Buying Decisions in the Local Fashion Brands: The Impact of Social Media Marketing, Brand Image, and Product Quality - Alwan Rafi Priambudi; Wilma Cordelia Izaak (Fakultas Ekonomika dan Bisnis Universitas 17 Agustus 1945 Semarang, 2026)
The increasing competition in Indonesia’s local fashion industry requires brands to strengthen their marketing strategies and better understand consumer behavior. Despite its rapid store expansion, Suko experienced declining sales, indicating a gap between business growth and consumer buying decisions. Furthermore, previous studies have reported inconsistent findings regarding the impact of social media marketing on buying decisions. Grounded in the Theory of Planned Behavior (TPB), this study examines how social media marketing, brand image, and product quality impact the buying decisions of Generation Z consumers in Surabaya toward Suko products. A quantitative method was conducted through a survey questionnaire involving 145 respondents aged 17–29 years in Surabaya who had previously buying and used Suko clothing products. The respondents were selected through purposive sampling and were processed using PLS-SEM. The results show that social media marketing, brand image, and product quality simultaneously and partially have a positive and significant impact on buying decisions, with brand image having the strongest impact. These findings extend the application of the TPB framework in the context of local fashion brands and provide practical insights for Suko to strengthen its marketing strategies by enhancing social media engagement, a positive brand image, and reliable product quality to shaping Generation Z buying decisions.